2001
DOI: 10.1208/ps030432
|View full text |Cite
|
Sign up to set email alerts
|

The cytoplasmic escape and nuclear accumulation of endocytosed and microinjected HPMA copolymers and a basic kinetic study in hep G2 cells

Abstract: The development of macromolecules as drugs and drug carriers requires knowledge of their fate in cells. To this end, we studied the internalization and subcellular fate of N-(2-hydroxypropyl)methacrylamide (HPMA) copolymers in Hep G2 (human hepatocellular carcinoma) cells. Semiquantitative fluorometry confirmed that galactose was an effective ligand for receptormediated endocytosis for Hep G2 cells. The rate of internalization of a galactose-targeted copolymer was almost 2 orders of magnitude larger than that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 40 publications
3
16
0
Order By: Relevance
“…Such a result is not without precedence. Jensen et al have reported the cytoplasmic localization and nucleus entry of HPMA copolymers in Hep G2 cells before. After 24 h of incubation, the green fluorescence remains unchanged, but the red fluorescence of DOX exhibited a similar distribution as free DOX, indicating that the released DOX acts the same function as free DOX.…”
Section: Results and Dissusionmentioning
confidence: 99%
“…Such a result is not without precedence. Jensen et al have reported the cytoplasmic localization and nucleus entry of HPMA copolymers in Hep G2 cells before. After 24 h of incubation, the green fluorescence remains unchanged, but the red fluorescence of DOX exhibited a similar distribution as free DOX, indicating that the released DOX acts the same function as free DOX.…”
Section: Results and Dissusionmentioning
confidence: 99%
“…Because drug-polymer conjugates are not easily recognized by their receptors, their therapeutic activity depends mainly on the amount of free drug released from the conjugate. It usually takes longer for non-targeted polymer-drug conjugates, such as P-Dex, to be endocytosed and incorporated into the lysosomes where the acidic environment would act to release the Dex [37]. The free Dex must then escape from the lysosomal compartment to deliver its anti-inflammatory effect.…”
Section: Discussionmentioning
confidence: 99%
“…4B), contains N-acylated galactosamine (GalN), which was designed to be recognized by ASGPR in HepG2 human hepatocellular carcinoma cells (59,82) and individual members of the galectin family (e.g., galectin-3) in human colon adenocarcinoma (83,84). Galectin-3 is expressed in normal tissues and highly expressed in neoplastic tissues (85–87); although the exact opposite has been shown to occur (88,89).…”
Section: Cat B-cleavable Dox Prodrugsmentioning
confidence: 99%